Desmoid tumor: an unusual case of gross hematuria - Isharwal, Sudhir (Ther Adv Urol, 2015)
Desmoid tumors are rare soft-tissue masses originating from the proliferation of fibroblasts in the fibroconnective tissues. Intra-abdominal desmoid tumors pose special diagnostic challenge due to multiplicity of differential diagnoses, and difficulty to well characterize the lesions on imaging studies. Desmoid tumors can have atypical presentation making clinical correlation challenging to unsuspecting urologists. Only a few cases have been reported in the urology literature. In this report, we present a case of desmoid tumor presenting with gross hematuria.